Erkek köpeklerde intratestiküler gliserol ve etanol uygulamalarının kısırlaştırma üzerine etkilerinin karşılaştırılması (Comporation of the Effects of Intratesticular Glycerol and Ethanol Injections on Sterilization of Male Dogs) - Günay, C; Sağlıyan, A; Yaman, İ; Sönmez, M; Türk, G (My University, 2004)
This study was conducted to investigate the effects of intratesticular glycerol and ethanol injection on sterilization. Twelve mature male dogs were used. They were allocated randomly to two equal groups called glycerol and ethanol and one ml glycerol (70%) and ethanol (95%) was injected intratesticularly. The animals were observed during two months. The blood and sperm samples obtained once a week in all groups were examined regarding to serum testosterone level and spermatozoon concentration and motility rate. There was a fistula formation and scrotal wounds resulting from orchitis in all glycerol and two ethanol group dogs after the 5th day of injection. The fistular openings closed spontaneously in all cases in due course. After the 2nd month, testicular atrophy was seen to occur. It was determined the presence of marked decreases (p<0.01) in both groups spermatozoon concentration and motility as well as in the level of serum testosterone two weeks after drug injection. The histopathologic examination conducted after the 2nd month revealed degeneration, necrosis and diffuse connective tissue proliferation in the seminiferus contortus tubulus of both groups. It has been concluded that glycerol and ethanol can be effective for sterilization in male dogs.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Gliserol Etanol Kısırlaş tırma Erkek Köpek (Glycerol; Ethanol; Sterilization; Male Dog).